2022
DOI: 10.5650/jos.ess21424
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocin Production by <i>Lactobacilli</i> and Their Role as Antibacterial Tool against Common Pathogens

Abstract: IntroductionLactic acid bacteria are abundantly found in food and also found in the digestive tract of animals and humans 1) . The term Lactobacillus was increasingly being acknowledged in early 20 th century 2) . All strains of LAB are categorized as probiotics however, the members of two genera Lactobacillus sp. and Bifidobacterium sp. are a having vast number of probiotics 3) . But most of the probiotics belong to the genus Lactobacillus 4) . Activity against undesirable and pathogenic bacteria is the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The results agreed with [28] who reported the high ability of L. crispatus and L. parabuchneri to adhere with S. mutans which reached 71.66% after 5 hrs. The obtained result was also in agreement with study that reported the ability of Lactobacillus to co-aggregate with pathogens [33]. According to the definition by the World Health Organization (WHO) and the American Food and Agricultural Organization (FAO), a probiotic is "a live organism which has a beneficial effect on human health when they take in enough amounts" [34].…”
Section: Resultssupporting
confidence: 89%
“…The results agreed with [28] who reported the high ability of L. crispatus and L. parabuchneri to adhere with S. mutans which reached 71.66% after 5 hrs. The obtained result was also in agreement with study that reported the ability of Lactobacillus to co-aggregate with pathogens [33]. According to the definition by the World Health Organization (WHO) and the American Food and Agricultural Organization (FAO), a probiotic is "a live organism which has a beneficial effect on human health when they take in enough amounts" [34].…”
Section: Resultssupporting
confidence: 89%
“…P. acidilactici R9 and P. pentosaceus R10 also exhibited strong inhibitory abilities, with their inhibitory effects being more prominent against Gram-negative bacteria compared to Gram-positive bacteria. However, L. fermentum and L. paracasei displayed the weakest inhibitory abilities, particularly against Gram-positive bacteria, which is similar to the findings of Trindade et al (2022) and Younas et al (2022) . This is seemingly attributed to the ability of LAB in inhibiting or eradicating biofilms ( Shokri et al, 2018 ; Ibrahim et al, 2021 ), a mechanism that proves more challenging when confronted with the thicker peptidoglycan cell wall structure characteristic of Gram-positive bacteria.…”
Section: Resultssupporting
confidence: 80%
“…L. lactis subp. lactis and L. plantarum mainly harbor non-enterocin genes, such as curvacin A, plantaricin A, sakacin P, and nisin [ 79 ] which might explain the absence of investigated enterocin genes in the two out of the three L. lactis subp. Lactis and the L. plantarum isolate.…”
Section: Resultsmentioning
confidence: 99%